OPTIMIZING IMMIGRATION PUBLIC SERVICES THROUGH ADMINISTRATIVE AUTHORITY AT BATAM IMMIGRATION CHECKPOINTS - Ahmad Rifki; Soerya Respationo; Siti Nurkhotijah; Erniyanti; Ramlan (PT. Radja Intercontinental Publishing, 2026)
services through administrative authority at the Batam Center Port Immigration Checkpoint (TPI), identify the accompanying obstacles, and formulate relevant policy solutions. Research Methodology: The research uses an empirical juridical approach (socio-legal research) with qualitative methods, combining legislative, conceptual, case, and socio-legal approaches, through semi-structured interviews with immigration officials, field observations on the implementation of digital-based international arrival reporting, and document studies at the Batam Class I Special Immigration Office TPI. Results: The administrative authority of Immigration Officers at the Batam Center TPI has strong legal legitimacy through attribution, delegation, and mandate mechanisms, but the implementation of digital services via the All Indonesia Application is not optimal due to regulatory gaps, the absence of imperative administrative sanction norms, and the unavailability of standard Contingency Plan SOPs. The Reliability Dimension has not been achieved due to server latency during peak hours, while the Responsiveness Dimension of officers is high but functions as a compensating factor that shifts the role of officers from border law enforcement to technical assistance. From the perspective of Aristotle's Theory of Justice, a single digital service scheme has the potential to harm distributive justice for vulnerable groups, while corrective justice for system failures is still ad-hoc because it has not been institutionalized. Conclusion: Optimizing immigration public services at TPI Batam Center requires holistic legal and bureaucratic engineering in three dimensions at once, namely legal substance, legal structure, and legal culture, as per the Friedman Legal System Theory framework, so that the balance of the Four Immigration Functions can be realized without sacrificing state security or the quality of public services. Limitations: The research is limited to one locus, namely the Batam Center Port TPI, with qualitative data based on interviews with a limited number of informants, so generalizations to other TPIs with different characteristics need to be done carefully. Contribution: This research contributes to the development of state administrative law and immigration law, particularly regarding administrative authority in digital border governance, and proposes concrete recommendations for the Directorate General of Immigration and the Batam Immigration Office.